Urgensi Program Muhadhoroh dalam Meningkatkan Kemampuan Public Speaking Santri Pondok Pesantren Al-Fatah Cileungsi (Studi Kasus Santriwan MTS Al-Fatah Cileungsi) - Syahrul Fauzi Kurniawan; Asep Gunawan; Falizar Rivani (Universitas Pahlawan Tuanku Tambusai, 2023)
Pondok Pesantren Al-Fatah Cileungsi as an Islamic educational institution has an important role in the formation of the center character. One important aspect of self-centric development is public speaking, which is a vital skill in effective communication. The study aims to identify the urgency of the Mahadhoroh program in improving the public speaking capabilities of civilians in the Pondok Pesantren Al-Fatah Cileungsi.The research method used is a qualitative approach to data collection techniques through observations, interviews, and documentation analysis. Respondents of the study involved the Chancellor of Pondok Pesantren Al-Fatah Cileungsi who followed the Mahadhoroh program. The results of this study are expected to provide an in-depth understanding of the extent to which the Mahadhoroh program contributes to the improvement of public speaking skills.This research found that the Mahadhoroh program has a significant urgency in improving the public speaking ability of the centri. Muhadhoroh provides a platform for practising speaking in public, boosting confidence, and developing argumentation skills. In addition, through Mahadhoroh, the centurion can better understand Islamic values and apply them in the context of communication. The Muhadhoroh program has proved to have a significant role in improving the ability of the public speaking centers and the urgency of the activities of the Muhadharoh is enormous in the context of the development of public speech centers. It is not only an additional skill, it is also a valuable investment in the preparation of the centers to face the communication challenges in various sections of society.